Role of Digital Forensics in Combating Financial Crimes in the Computer Era (The Journal of Forensic Accounting Profession, 2023)
Information and communication technologies (ICT) have changed every area of our lives. Cyberspace-related areas have reflected these shifts. Cyberspace has an undeniable positive impact on information, trade, industry, and communication. On the other hand, cybercrime is a dark side of the Internet that degrades its peaceful use. Any illegal activity carried out by or via cyberspace and its electronic environment is characterized as cybercrime. Unlike traditional crimes, cybercrimes present a real dilemma because the identities of criminals may be hidden in the virtual domain. Digital forensics has emerged to formulate possible ways for cybercrime investigation and analysis process. In this paper, we deplore the idea of digital forensics in the context of cybercrimes. An investigation of the positive impact of digital forensics in combating cybercrimes is discussed. In today’s world of computers, any information can be made available within a few clicks for different endeavors. The information may be tampered with by changing the statistical properties and can be further used for criminal activities.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2023-0003, pod licencom CC BY-NC-ND 4.0)
Keywords: digital forensics; combating financial crimes; computer era